Helicase binding to DnaI exposes a cryptic DNA-binding site during helicase loading in Bacillus subtilis - Ioannou, Charikleia; Schaeffer, Patrick M.; Dixon, Nicholas E.; Soultanas, Panos (Oxford Journals, 2006)
The Bacillus subtilis DnaI, DnaB and DnaD proteins load the replicative ring helicase DnaC onto DNA during priming of DNA replication. Here we show that DnaI consists of a C-terminal domain (Cd) with ATPase and DNA-binding activities and an N-terminal domain (Nd) that interacts with the replicative ring helicase. A Zn2+-binding module mediates the interaction with the helicase and C67, C70 and H84 are involved in the coordination of the Zn2+. DnaI binds ATP and exhibits ATPase activity that is not stimulated by ssDNA, because the DNA-binding site on Cd is masked by Nd. The ATPase activity resides on the Cd domain and when detached from the Nd domain, it becomes sensitive to stimulation by ssDNA because its cryptic DNA-binding site is exposed. Therefore, Nd acts as a molecular 'switch' regulating access to the ssDNA binding site on Cd, in response to binding of the helicase. DnaI is sufficient to load the replicative helicase from a complex with six DnaI molecules, so there is no requirement for a dual helicase loader system.